Influencia del reciclaje de residuos sólidos en la promoción sanitaria de los pobladores que participan en el programa de la municipalidad de chepen: 2015 - Quispe Revilla, Gretta (2015)
This thesis was carried out with the purpose to analyze the influence of the recycling of solid waste in the health promotion for the people who participate in the Program of the Provincial Municipality of Chepen, in 2015. It has been considered the type of applied research on the basis of an explanatory design, and the sample consisted of 77 recyclers, with which work by applying the methods and techniques of quantitative and qualitative research. That goal was fulfilled with the results found in the qualitative and quantitative study. The results of this research show that the management of collection, selection, and marketing of solid waste contributes to the prevention of the health of the inhabitants of the City of Chepen. In addition it has been shown that the recycling of solid waste promotes health education and environmental awareness to prevent contagious diseases in the population of Chepen.